2019
DOI: 10.1002/bio.3627
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the effect of halide ions on the fluorescence of quinine sulfate

Abstract: The effect of halide ions (Cl − , Br − and I − ) on the fluorescence of quinine sulfate in dilute sulfuric acid solution was studied by fluorescence spectra, ultraviolet-visible (UV-visible) absorption spectra and fluorescence decay technique. The results exhibited that halide ions with heavier atomic mass could significantly reduce the fluorescence intensity of quinine sulfate, as a result, the order of fluorescence quenching caused by halide ions is Cl − < Br − < I − . Therefore, halide ions with high concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The two halides, chloride and iodide, differ in their ionic radii as well as their quenching potency, which has been correlated to their ionization energies . Chloride has an ionic diameter of about 334 pm, while iodide has an ionic diameter of approximately 412 pm and is a stronger quencher. Experiments were performed using the DNA–RNA oligonucleotides GXC, TXA, and CXA (Figures and S8, and Table ). GXC was the brightest sequence observed, while TXA and CXA showed the most pronounced fluorescence increase in A-form DNA–RNA duplexes relative to fluorescence in B-form dsDNA.…”
Section: Resultsmentioning
confidence: 99%
“…The two halides, chloride and iodide, differ in their ionic radii as well as their quenching potency, which has been correlated to their ionization energies . Chloride has an ionic diameter of about 334 pm, while iodide has an ionic diameter of approximately 412 pm and is a stronger quencher. Experiments were performed using the DNA–RNA oligonucleotides GXC, TXA, and CXA (Figures and S8, and Table ). GXC was the brightest sequence observed, while TXA and CXA showed the most pronounced fluorescence increase in A-form DNA–RNA duplexes relative to fluorescence in B-form dsDNA.…”
Section: Resultsmentioning
confidence: 99%
“…If pyrene undergoes a more facile ISC to a triplet state due to interactions with halides, it would then be expected to be less subject to photo-oxidation. Another study, which looked at quinine in a solution of sulfuric acid, also demonstrated the heavy atom effect on the fluorescence quenching, although the authors note that the fluorescence quenching of quinine could be by a dynamic and static quenching mechanism. In both cases, the effects are shown to be strongly related to the ability of the halide to alter the n-pi* energy separation of the quinoline ring, which facilitates ISC to the triplet electronic state …”
Section: Discussionmentioning
confidence: 99%
“…15−18 Common quenchers that are found in natural waters are metals, singlet oxygen, and halides. 19−22 In particular, halides show a strong quenching ability toward several other organic molecules, such as quinine, 20 metal porphyrins, 24 and polyaromatic hydrocarbons. 25 In this fundamental study, we use a Stern−Volmer analysis to quantify the chlorophyll fluorescence quenching by common seawater components as well as that of an artificial seawater solution at a natural seawater salinity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excitation spectra were measured in the wavelength range of 250−370 nm and the emission wavelength was 332 nm. The wavelength ranges were selected based on the literature [ 19,20 ] and adjusted according to the previous measurements. The scan speed was 6000 nm min –1 and the interval was 1 nm.…”
Section: Methodsmentioning
confidence: 99%